2019
DOI: 10.3389/fimmu.2019.01037
|View full text |Cite
|
Sign up to set email alerts
|

Role of Neutrophil Extracellular Traps and Vesicles in Regulating Vascular Endothelial Permeability

Abstract: The microvascular endothelium serves as the major barrier that controls the transport of blood constituents across the vessel wall. Barrier leakage occurs during infection or sterile inflammation, allowing plasma fluid and cells to extravasate and accumulate in surrounding tissues, an important pathology underlying a variety of infectious diseases and immune disorders. The leak process is triggered and regulated by bidirectional communications between circulating cells and vascular cells at the blood-vessel in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(97 citation statements)
references
References 120 publications
0
96
0
1
Order By: Relevance
“…Likewise, I/R significantly elevated lung MPO levels, an effect attenuated by MLDL ( Figure 2B). Trans-endothelial migration of neutrophils involves the opening of endothelial barrier, causing increased permeability (2). Lung microvascular permeability, evaluated by Evans blue extravasation, was markedly elevated after gut I/R, and this effect was ameliorated by MLDL ( Figure 2C).…”
Section: Mldl Attenuates Intestinal I/r-induced Neutrophil Infiltratimentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, I/R significantly elevated lung MPO levels, an effect attenuated by MLDL ( Figure 2B). Trans-endothelial migration of neutrophils involves the opening of endothelial barrier, causing increased permeability (2). Lung microvascular permeability, evaluated by Evans blue extravasation, was markedly elevated after gut I/R, and this effect was ameliorated by MLDL ( Figure 2C).…”
Section: Mldl Attenuates Intestinal I/r-induced Neutrophil Infiltratimentioning
confidence: 99%
“…During the process of neutrophil diapedesis, CD11b on neutrophil surface is upregulated and binds to endothelial adhesion molecules to form firm adhesion (2). We treated normal mouse whole blood with pre-I/R or post-I/R lymph, and measured neutrophil CD11b expression using multicolor flow cytometry.…”
Section: Post-i/r Lymph But Not Pre-i/r Lymph Increases Neutrophil mentioning
confidence: 99%
See 1 more Smart Citation
“…During the ARDS process, activated neutrophils release intracellular toxic components so as to amplify the inflammatory response by recruiting more inflammatory cells into the site of damage [34]. Additionally, Ma et al [35] reported that neutrophils were involved in regulating the microvascular endothelial permeability. Suzuki et al [36] reported that neutrophil elastase damaged the pulmonary endothelial glycocalyx in LPS-induced endotoxemia.…”
Section: Figmentioning
confidence: 99%
“…Mast cells are implicated especially as a source of histamine. There is interest in neutrophil products and especially in the possibility that these cells participate in more sustained plasma leaks [70, 71]. Once extravasated, additional plasma-derived players, typically kininogen-produced bradykinin [72, 73], may contribute.…”
Section: Plasma Exudation and Exudative Hyperresponsiveness At Viral mentioning
confidence: 99%